ANALYSIS OF CONSUMERS' WILLINGNESS TO PAY FOR THE PURCHASE OF BEN ALI MORINGA LEAF TEA IN NORTH ACEH DISTRICT - Dhuhratulliza Dhuhratulliza; Adhiana Adhiana; Irada Sinta (Jurnal Mahasiswa Agribisnis, 2024)
Analysis Of Consumers' Willingness To Pay For The Purchase Of Ben Ali Moringa Leaf Tea In North Aceh District. This research was conducted at Sabanna Lhokseumawe, Ichsan Mart Lhoksukon, Sinar Baru Panton, Rayon Panton, Kardana Mart Panton, and Berkah Mart Panggoi stores. The selection of this location was done intentionally (Purposive). The object of this research is consumers who consume moringa leaf tea. The scope of this research only looks at how much consumers are willing to pay for the purchase of moringa tea and the factors that influence the willingness to pay.  Consumer willingness to pay for Ben Ali Moringa moringa tea shows that all respondents in this study stated that they were willing to pay more for moringa tea products. The willingness to pay resulted in an average analysis value of WTP (Willingness to Pay) for original moringa tea and red ginger of IDR 1,916 with a price determination that consumers were willing to pay of 1000. This means that the increase in the price of moringa tea from the previous price was IDR 26,916 for the original variant and IDR 36,916 for the red ginger variant. Factors affecting consumer willingness to pay for Ben Ali Moringa Moringa tea in North Aceh Regency were analyzed using a binary logistic regression model, of the 4 independent variables entered into the model there are three variables that have a significant effect on willingness to pay with a significant level of Î± (0.05), These variables are income (X2), Lifestyle (D3) and Ease of Access (D4). While the Age variable (X3) does not have a significant effect on willingness to pay for Ben Ali Moringa Moringa tea.